The science of handcycling: a narrative review - Nevin, J.; Kouwijzer, I.; Stone, B.; Quittmann, O. J.; Hettinga, F.; Abel, T.; Smith, P. M. (International Journal of Sports Physiology and Performance, 2022)
The aim of this narrative review is to provide insight as to the history, biomechanics, and physiological characteristics of competitive handcycling. Furthermore, based upon the limited evidence available, this paper aims to provide practical training suggestions by which to develop competitive handcycling performance. Handbike configuration, individual physiological characteristics, and training history all play a significant role in determining competitive handcycling performance. Optimal handcycling technique is highly dependent upon handbike configuration. As such, seat positioning, crank height, crank fore-aft position, crank length, and handgrip position must all be individually configured. In regard to physiological determinants, power output at a fixed blood lactate concentration of 4 mmol·L-1, relative oxygen consumption, peak aerobic power output, relative upper body strength, and maximal anaerobic power output have all been demonstrated to impact upon handcycling performance capabilities. Therefore, it is suggested that that an emphasis be placed upon the development and frequent monitoring of these parameters. Finally, linked to handcycling training, it is suggested that handcyclists should consider adopting a concurrent strength and endurance training approach, based upon a block periodization model that employs a mixture of endurance, threshold, interval, and strength training sessions. Despite our findings, it is clear that several gaps in our scientific knowledge of handcycling remain and that further research is necessary in order to improve our understanding of factors that determine optimal performance of competitive handcyclists. Finally, further longitudinal research is required across all classifications to study the effects of different training programs upon handcycling performance.